Comparison between serum pleural effusion albumin gradient, total protein, lactate dehydrogenase, and erythrocyte count in malignant and non-malignant pleural effusion - Victor Nugroho Wijaya; I Gede Ketut Sajinadiyasa; Ni Wayan Candrawati; Ida Ayu Jasminarti Dwi Kusumawardani; Ni Luh Putu Eka Arisanti; I Gusti Ngurah Bagus Artana; Ida Bagus Ngurah Rai (Intisari Sains Medis, 2022)
Background: Malignant pleural effusion carries a bad prognosis. Pathologic examination as the gold-standard diagnosis of malignant pleural effusion has sensitivity limitations and may cause delayed diagnosis. Several affordable examinations, such as serum pleural effusion albumin gradient, total protein, lactate dehydrogenase (LDH), and erythrocyte count, might be useful as malignant pleural effusion diagnostic tools. Methods: This is an observational analytic study with a cross-sectional design conducted at Sanglah Central General Hospital in Denpasar from December 2021 to July 2022. Pleural effusion fluid and blood were taken from subjects with malignant and non-malignant pleural effusion. Data were analyzed with SPSS version 25 software for Windows. Results: Total subjects were 47 persons consisting of 26 subjects with malignant pleural effusion and 21 subjects with non-malignant pleural effusion. Results from statistical analysis of malignant and non-malignant pleural effusion were serum pleural effusion albumin gradient median (IQR) 0.91 (0.65) g/dL vs. 1.22 (1.2) g/dL (p=0.129), total protein mean 3.92±0.95 g/dL vs. 3.52±1.67 g/dL (p=0.334), LDH median 535 (840) IU/L vs. 187 (1,016) IU/L (p=0.057), and erythrocyte count median 23,500 (109,250) cells/mm3 vs. 3,000 (11,000) cells/mm3 (p=0.004). The AUC of erythrocyte count from the ROC method was 0.745 (95%CI=0.599-0.890; p=0.004). Using a cut-off point ≥ 4,500 cells/mm3, it had a sensitivity of 80.8%, specificity of 61.9%, and Odds Ratio (OR) of 6.8 (95%CI=1.8-25.4). Conclusion: Erythrocyte count as routine examination showed good validity for diagnosing malignant pleural effusion and expected to reduce diagnosis delay. Meanwhile, albumin gradient, total protein, and LDH delivered no difference.